A facile method to fabricate tough hydrogel with ultra‐wide adjustable stiffness, stress, and fast recoverability. Issue 21 (19th September 2018) - Xiang, Shuangfei; Li, Ting; Dong, Weifu; Lu, Qinghua
ABSTRACT: In this article, we report a synergistic strategy to develop dual physically cross‐linked tough hydrogels via one‐pot bulk copolymerization of N‐vinyl‐2‐pyrrolidone, acrylic acid, and stearyl methylacrylate (SMA) without any adscititious surfactant. Due to synergic effects of hydrogen bonding and hydrophobic association, the resulted dual physically cross‐linked hydrogels (DP Gel) with ultra‐wide range adjustable Young's modulus (0.08–45.6 MPa), tensile stress (0.7–6.9 MPa), and toughness (3.3–23.1 MJ m −3 ). Stretching to 300%, DP Gel exhibited fast recoverability that remained ~95% of initial dissipated energy after resting in 60 °C for 3 min. Finally, scanning electron microscopy revealed that the microstructure of hydrogel changed from phase separation structure to micro phase separation as SMA added, which accounted for excellent performance of DP Gel. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1469–1474 Abstract : A facile method to fabricate dual physically cross‐linked hydrogels with ultra‐wide range adjustable Young's modulus (0.08–45.6 MPa), tensile stress (0.7–6.9 MPa), toughness (3.3–23.1 MJ·m −3 ), and fast recoverability is presented. The hydrogel was developed via a one‐pot bulk copolymerization of N‐vinyl‐2‐pyrrolidone (NVP), acrylic acid (AAc), and stearyl methylacrylate (SMA) without any added surfactant.